Algunas plantas interesantes de Andalucía oriental (Málaga-Granada) - Cabezudo, Baltasar; Pérez Latorre, Andrés V.; Casimiro-Soriguer Solanas, Federico; Pavón, Manuel; Hidalgo Triana, Noelia (Acta Botanica Malacitana, 2011)
Some interesting plants from Eastern Andalusia (Malaga-Granada) Palabras clave. Flora, novedades, Andalucía, España. Key words. Flora, new records, Andalusia, Spain.